2014
DOI: 10.1016/j.jare.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Profile of cystic fibrosis in a single referral center in Egypt

Abstract: It was generally believed that Cystic fibrosis (CF) is rare among Arabs; however, the few studies available from Egypt and other Arabic countries suggested the presence of many undiagnosed patients. The aim of the present study was to determine the frequency of CF patients out of the referred cases in a single referral hospital in Egypt. A total of 100 patients clinically suspected of having CF were recruited from the CF clinic of the Allergy and Pulmonology Unit, Children’s Hospital, Cairo University, Egypt, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 27 publications
4
24
2
Order By: Relevance
“…Limited data are available about CF in Egypt. Only two recently published articles highlighted the presence of many cases assuming that it is not uncommon in Egypt (Naguib et al 2007 ; El-Falaki et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited data are available about CF in Egypt. Only two recently published articles highlighted the presence of many cases assuming that it is not uncommon in Egypt (Naguib et al 2007 ; El-Falaki et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study addressed the most common CFTR mutations in another 60 CF patients different from those included in our previous study (El-Falaki et al 2014 ). Most of patients included in the sample had typical clinical manifestations of repeated chest infection, variable pulmonary disease, steatorrhea, failure to thrive and early liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to data reported from Europe and USA where CF patients are usually diagnosed in first year of life. El-Falaki et al showed similar results with majority of patients had symptoms in first year of life and diagnosis was made after second year of life 9. This delay is partly due to lack of rationalizing CF by health care provider as an important differential diagnosis and partly by non-availability of facilities assistingearly diagnosis 10.…”
Section: Discussionmentioning
confidence: 86%
“…6 Since then, more than 2,000 mutations in CFTR gene have been reported, of which two nonsense mutations (G542X and W1282X) are relatively common in Egypt and other countries. 7,8 However, several cases with positive genetic tests may not fit into the full diagnostic criteria for CF (CFTR-related disease or syndrome) and can present with chronic rhinosinusitis, recurrent wheezes, or cough 9 and can be a cause of poor asthma control.…”
Section: Introductionmentioning
confidence: 99%